„Trznadle” Denisa Osokina: tradycja, rytuał, fikcja - Raspapou, Aliaksandr (Studia Rossica Posnaniensia, 2012)
In this article we will attempt to take a close look at the artistic output and literary phenomenon of Denis Osokin, one of the most unique writers of the new generation in contemporary Russian literature. Based on The Buntings, Osokin’s most important novel, we will attempt to discuss the subject matter, literary genre and selected problems in the author’s poetics and philosophy. What is most interesting today in Russian literature takes place here – in short forms, along the thin line between poetry and prose, and outside of existing forms, which is exemplified by The Buntings.